THE INFLUENCE OF PRODUCT QUALITY AND SERVICESCAPE TOWARDS CUSTOMER SATISFACTION AT KOPI KOPI CAFÉ MANADO - Rattu, Kezia; Lapian, S.L.H.V Joyce; Saerang, Regina Trifena (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study examines the impact of product quality and servicescape on customer satisfaction, focusing on the mediating role of customer satisfaction. The findings indicate that both product quality and servicescape significantly influence customer satisfaction. Enhanced customer satisfaction is associated with high product quality and an appealing servicescape. The study concludes that improving these aspects can lead to higher customer satisfaction at Kopi Kopi Manando Café.   Keywords: Product Quality, Servicescape, Customer Satisfaction